Artscience Museum an Embedded Stand-Alone Art - Amy Amelia Binte Ahmad Ahmad (Journal La Multiapp, 2020)
This paper reviews and analyses the process and built-up of the ArtScience Museum. It touches on the history, building features and Moshe Safdie’s design approach in forming the museum’s architecture. Furthermore, it explores the motivations in having a cultural institution within the Marina Bay precinct and the correlation of what it was intended to be with the identity it has formed today. The Art Science Museum can be seen as a form of an add-on to Marina Bay Sands as the tender competition project included a design for a cultural institution. However, despite it being a form of enhancement, the ArtScience Museum arose and served its purpose being an intriguing form of architecture and a place for learning for people alike.